Molecular dynamics simulation of the dynamical mechanical analysis of polybutadiene. (July 2022) - Ebrahimi, Sadollah; Meunier, Marc; Soldera, Armand
Abstract: Dynamical mechanical analysis (DMA) is an experimental technique to characterize the viscoelastic behavior of thermoplastic polymers versus the frequency, temperature, etc. However, from an atomistic simulation viewpoint, DMA has not been much investigated. In this study we propose to fill this gap. Dynamical and mechanical properties of polymers have thus been investigated using atomistic simulation to characterize the viscoelastic response of 1, 4-Polybutadiene (PBD), an important synthetic rubber. For this, the dynamic moduli of the 1, 4-Polybutadiene (PBD) at different regimes have been analyzed considering two different methods using molecular dynamics simulations with GPU acceleration: one based on Green-Kubo expression, and the second one on calculating stress response in a cyclic deformation. The frequency-dependent complex shear modulus and dynamic viscosity of PBD have thus been reported. Our findings will aid future research in more accurate prediction of dynamical and mechanical properties of novel viscoelastic materials. Highlights: Two methods, Green-Kubo, and stress time series are used to calculate the dynamic moduli. The stress time series is a reliable approach to extract the complex shear modulus. Thermograms can be obtained by using stress time series approach. The calculated dynamic viscosities confirm the reliability of stress time series approach.